(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the effect of coexistent extracapsular extension and seminal vesicle invasion on biochemical reccurence free survival rates in patients who had undergone open radical retropubic prostatectomy.Material and Methods: The data of 307 patients with clinically localized prostate cancer who had undergone radical retropubic prostatectomy between January 2000 and May 2019 were evaluated retrospectively. According to extension of tumor on surgical specimens, patients were classified into five groups as; organ-confined disease, extracapsular extension, isolated seminal vesicle invasion, extracapsular extension in addition to seminal vesicle invasion and lymph node involvement. Patient groups were analyzed categorically with regard to biochemical reccurence free survival rates by using Kaplan Meier analysis, log-rank and chi-square tests. The effect of pathological features of surgical specimens on biochemical reccurence was evaluated by using univariate and multivariate Cox regression analysis.Results: There were statistically significant differences on biochemical reccurence free survival rates among the five groups, and pathological stage and biochemical reccurence rates increased correspondingly. Multivariate Cox regression analysis showed that coexistent extracapsular extension and seminal vesicle invasion, and lymph node involvement are the two significant factors that negatively effect the biochemical reccurence free survival rate.Conclusion: Coexistence of extracapsular extension and seminal vesicle invasion is a worse prognostic factor compared to their isolated forms.